Concussion-Reporting Behavior in Rugby: A National Survey of Rugby Union Players in the United States. Issue 1 (20th January 2021) - Miller, J. Chance; Stein, Kenneth Shubin; Moon, Tyler J.; Trofa, David P.; Kerr, Hamish; Bottiglieri, Thomas; Ahmad, C.S.
Background: Rugby is the fastest growing team sport in the United States for male and female athletes. It is a contact/collision sport with an injury risk profile that includes concussions. Purpose: To examine the prevalence of concussions in male and female rugby players in the United States and to characterize behaviors around reporting concussions that could be a target for prevention and treatment efforts. Study Design: Cross-sectional study; Level of evidence, 3. Methods: An online survey distributed to active members on the USA Rugby membership list was used to examine self-reported concussions in male and female athletes. Concussion-reporting behaviors and return to play after a concussion were also explored. Statistical analysis was used to compare male with female athletes and report differences, with years of experience as a dependent variable. Results: The proportion of athletes with a history of at least 1 concussion was 61.9% in all respondents. Of those who reported a concussion, 50.8% reported the concussion during the game or practice in which it occurred, and 57.6% reported at least 1 concussion to a qualified medical provider. Overall, 27.7% of participants who reported ≥1 rugby-related concussion in our survey noted that at least 1 of these concussions was not formally reported. The most commonly cited reasons for not reporting a concussion included not thinking that it was a serious injury, not knowing that it was a concussion at the time, and not wanting to be pulled out of the game or practice. Additionally, 61.0% of athletes did not engage in recommended return-to-play protocols after their most recent rugby-related concussion. Conclusion: US rugby union athletes may not report concussions to medical personnel or follow return-to-play protocols guided by medical advice. This could result from a lack of education on concussion recognition and the risks associated with continued play after a concussion as well as limited access to health care. Further education efforts focusing on the identification of concussions, removal from play, and return-to-play protocols are necessary in the US rugby union population.